2020
DOI: 10.1002/osi2.1061
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between severity of obstructive sleep apnea and maxillofacial morphology and BMI; from the point of view of sex and age distribution

Abstract: Purpose Obstructive sleep apnea (OSA) is generally more common in men than in women, so many studies have only involved male OSA patients as subjects. However, a certain proportion of OSA patients are female, and few studies have addressed this population. Maxillofacial morphology and obesity are now being shown to be intimately connected with OSA, but the details remain unclear. The objective of this retrospective study was to identify the clinical features of OSA in men and women of different ages, with a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
2
0
0
Order By: Relevance
“…As age increases, the changes in the morphological characteristics in the upper airway may play a role in the development of OSA. It was also reported that the severity of the disease further increases with an increase in BMI 30 . This study demonstrated the significant association between obesity (BMI and NC) and increasing severity of OSA ( p < .001), which is consistent with the previously reported studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As age increases, the changes in the morphological characteristics in the upper airway may play a role in the development of OSA. It was also reported that the severity of the disease further increases with an increase in BMI 30 . This study demonstrated the significant association between obesity (BMI and NC) and increasing severity of OSA ( p < .001), which is consistent with the previously reported studies.…”
Section: Discussionsupporting
confidence: 92%
“…[25][26][27] Rogers et al reported a similar finding in a study that BMI or waist circumference could be the predictors associated with the risk of OSA in the Black population. 28 Our results in 30 This study demonstrated the significant association between obesity (BMI and NC) and increasing severity of OSA (p < .001), which is consistent with the previously reported studies.…”
Section: Ta B L Esupporting
confidence: 91%